2020
DOI: 10.1101/2020.09.28.20203083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of stopping therapy during the SARS-CoV-2 pandemic in persons with lymphoma

Abstract: Introduction: The severe acute respiratory syndrome-2 (SARS-CoV-2) pandemic disrupted medical care for persons with cancer including those with lymphoma. Many professional societies recommend postponing, decreasing or stopping anti-cancer therapy in selected persons during the pandemic. However, although seemingly sensible these recommendations are not evidence-based and their impact on anxiety and health-related quality-of-life (HRQoL) is unknown. Methods: Surveyed 2532 subjects including 1060 persons with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…These data suggest that persons with CML are psychologically vulnerable during the SARS-CoV-2 pandemic. Delay in monitoring response to TKI therapy, TKI therapy interruption, or dose reduction in persons with CML was associated with worse mental health in our study, consistent with the recent findings that treatment interruption, delay in cancer care, or reduced therapy intensity was associated with mental health problems and worse HRQoL in persons with cancer or lymphoma (12,13,(16)(17)(18)(40)(41)(42)(43). Fear of being infected with SARS-CoV-2 in the hospital or during travel as the common reason causing them not to follow the regular monitoring or cannot get TKI drugs in the hospital also reflected that they exaggerated the implementation of containment measures for avoidance of SARS-CoV-2 infection due to their psychological fragility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data suggest that persons with CML are psychologically vulnerable during the SARS-CoV-2 pandemic. Delay in monitoring response to TKI therapy, TKI therapy interruption, or dose reduction in persons with CML was associated with worse mental health in our study, consistent with the recent findings that treatment interruption, delay in cancer care, or reduced therapy intensity was associated with mental health problems and worse HRQoL in persons with cancer or lymphoma (12,13,(16)(17)(18)(40)(41)(42)(43). Fear of being infected with SARS-CoV-2 in the hospital or during travel as the common reason causing them not to follow the regular monitoring or cannot get TKI drugs in the hospital also reflected that they exaggerated the implementation of containment measures for avoidance of SARS-CoV-2 infection due to their psychological fragility.…”
Section: Discussionsupporting
confidence: 92%
“…There are many reports of increased prevalence and severity of mental health problems including those of depression, anxiety, and distress during the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic in the general population, medical health care workers (1)(2)(3)(4)(5)(6)(7)(8)(9), and persons with chronic diseases (10,11). Several studies reported that cancer patients experienced mental health problems or worse healthrelated quality of life (HRQoL) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21), which were associated with delay in cancer care or reduced therapy intensity. However, the impact of the pandemic on the mental health of persons with leukemia is rare, and there is none in persons with chronic myeloid leukemia (CML).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported anxiety amongst samples of all cancer patients during the pandemic [29,36,42,44]. Additionally, higher levels of anxiety were found amongst female patients in the UK, USA, Poland, and China [19,26,33,35,43,45]; patients from lower income households [11]; older and more vulnerable patients in the Netherlands and Northern Italy [18,30]; married patients in Singapore [36]; and patients with lower educational attainment in Italy, Singapore, and China [35,36,46]. In contrast, younger Chinese cancer patients demonstrated elevated levels of anxiety, suicide ideation, and low sleep quality, during the pandemic [47].…”
Section: Distress Anxiety and Depressionmentioning
confidence: 99%
“…These strategies were an important predictor of QoL [20] and positive health behaviours. Positive lifestyle choices were likely to alleviate mental health burden and improve HRQoL [30,35,54], while others employed avoidance coping strategies, including self-distraction and substance use [62].…”
Section: Innovations To Mitigate Impactsmentioning
confidence: 99%
“…The main concerns of patients with cancer during the COVID-19 pandemic have been the following: COVID-19 infection, access to cancer care in those newly diagnosed, and cancer recurrence and progression due to delayed treatment [6–8]. The psychological effects of COVID-19 infection in patients with cancer requires greater attention from caregivers and organizations, as these patients are often more vulnerable to mental disorders than the general population [9,10 ▪▪ ,11].…”
Section: Introductionmentioning
confidence: 99%